Comparative analysis between provided values and measured values on photovoltaic modules - Vinicius Puglia; Thadeu das Neves Conti (Brazilian Journal of Radiation Sciences, 2025)
This article aims to address a fundamental topic regarding photovoltaic modules, their respective performance. In the planning of a photovoltaic system, the power delivered by the module is the basis for project calculations, and it is investigated whether this value reflects reality. At Institute of Energy and Environment (IEE/USP), the I-V characteristic curve is plotted in a solar simulator to obtain the maximum values for two modules of different cell technologies compared to the values in the manufacturer’s datasheet. Additionally, electroluminescent images are also taken to corroborate possible distinctions between the measured values, as well as probable drops in their performance for photovoltaic systems. Thus, the analysis shifts from theoretical to practical with real numbers and curves that highlight any discrepancies that may exist in the stated description, as well as the accepted percentage with the respective tolerances.